Application of digital technologies in health literacy in situations of social isolation: a systematic review - Veiga, Nélio (2025)
Objective: Health literacy relates to the ability of individuals to acquire, understand, and, consequently, act in accordance with information provided to them to make appropriate decisions regarding their health status. About half of the European population has a low level of health literacy. Additionally, given the worsening state of isolation experienced by the COVID-19 pandemic, the aim of this systematic review was to analyze the impact of digital technologies on health literacy in situations of social isolation. Methods: A systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. The search strategies were based on the PICO question: “In contexts of social isolation (P), What is the impact (C) of digital technologies (I) on improving health literacy (O)?” An extensive electronic search was performed in three databases (PubMed/MedLine, Cochrane, and Web of Science (WoS)). Articles published in English, Portuguese, and Spanish languages from 2011 until 2021 were included; which approached social isolation, institutionalized or with pathologies that cause the need for dependence and care from others, studies that evaluate the impact of new technologies on improving health literacy, studies that compare aspects related to health literacy application strategies using new technologies, studies that demonstrated the impact of new technologies on improving the health literacy of populations in social isolation, and all types of studies, focusing essentially on observational studies, analytical studies, quasi-experimental and experimental studies. Results: Thirteen full-text articles were included in the study. Digital technologies were considered an intrinsic part of people's daily lives, having numerous advantages: allowing greater contact with family and friends, providing a moment of leisure and acquisition of knowledge, and contact with health professionals. In this way, new technologies have made it possible to increase users’ health literacy due to their easy access to information on various pathologies and health promotion measures. Conclusions: It is possible to conclude that the existence of individuals with access to digital media who are more able to acquire information about pathologies, their prevention, and treatment is related to better health conditions. Thus, health professionals' motivation for patients to use technological resources in the health component is essential. Moreover, the constant sharing of information on the internet, combined with the concept of telehealth and personalized monitoring by professionals in the field, has emphasized the importance of knowledge and health literacy.